2013
DOI: 10.2478/v10247-012-0068-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of uncultivated soils in derived savanna

Abstract: The spatial variability of some physicochemical properties of topsoils/subsoils under secondary forest, grassland fallow, and bare-soil fallow of three locations was evaluated. The data were analyzed and described using classical statistical parameters. Based on the coefficient of variation, bulk density, total porosity, 60-cm-tension moisture content, and soil pH were of low variability. Coarse and fine sand were of moderate variability. Highly variable soil properties included silt, clay, macroporosity, satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…This variability can be studied using CV in which case, ranking of CV of soil properties are grouped into different classes including least (< 15%), moderately (15 < 35%) and highly (> 35%) variable according to Wilding (1985). Obalum et al (2013) reported variation among soil properties under contrasting vegetation types in three different locations in southeastern Nigeria using CV. The range of the mean values of silt/clay ratio (SCR) of the soils was 0.73-0.91.…”
Section: Physical Properties Of Soilsmentioning
confidence: 99%
“…This variability can be studied using CV in which case, ranking of CV of soil properties are grouped into different classes including least (< 15%), moderately (15 < 35%) and highly (> 35%) variable according to Wilding (1985). Obalum et al (2013) reported variation among soil properties under contrasting vegetation types in three different locations in southeastern Nigeria using CV. The range of the mean values of silt/clay ratio (SCR) of the soils was 0.73-0.91.…”
Section: Physical Properties Of Soilsmentioning
confidence: 99%
“…Cocoa (Theobroma cacao L.) plantations have a problem of within-field yield variability which may originate form spatial variation is soil properties (Eneje et al, 2012;Obalum et al, 2013). Once established, cacao remains in the same field for decades, therefore cocoa fields are dominated with aging trees growing on variable and depleted soils (Snoeck et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This applies to points situated at small distance from each other. This should always be kept in mind when conducting studies using TDR gauges (Janik, 2008;Obalum at al., 2013). At the sites on the fallow (A and B) moisture content changes were similar.…”
Section: Resultsmentioning
confidence: 99%